2009
DOI: 10.1002/jcb.22175
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐8b induces growth and rich vascularization in an orthotopic PC‐3 model of prostate cancer

Abstract: Fibroblast growth factor 8 (FGF-8) is expressed at an increased level in a high proportion of prostate cancers and it is associated with a poor prognosis of the disease. Our aim was to study the effects of FGF-8b on proliferation of PC-3 prostate cancer cells and growth of PC-3 tumors, and to identify FGF-8b-associated molecular targets. Expression of ectopic FGF-8b in PC-3 cells caused a 1.5-fold increase in cell proliferation in vitro and a four- to fivefold increase in the size of subcutaneous and orthotopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…PCa cells were prepared in sterile Hank's buffered saline (Life Technologies) and injected (1×10 6 cells/40μL per mouse) orthotopically into 6-8wk old male athymic nude ( nu/nu ) mice (Harlan Sprague-Dawley) via the right dorsolateral lobe of the prostate as described [53, 54]. Briefly, a low midline abdominal incision of approximately 3-4 mm was made in anesthetized mice.…”
Section: Methodsmentioning
confidence: 99%
“…PCa cells were prepared in sterile Hank's buffered saline (Life Technologies) and injected (1×10 6 cells/40μL per mouse) orthotopically into 6-8wk old male athymic nude ( nu/nu ) mice (Harlan Sprague-Dawley) via the right dorsolateral lobe of the prostate as described [53, 54]. Briefly, a low midline abdominal incision of approximately 3-4 mm was made in anesthetized mice.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, high levels of FGF8 are expressed in prostatic [20][21][22] and testicular [23] cancers. Previous studies have shown that FGF8 can promote tumorigenic properties, such as growth, invasiveness, and the angiogenic, migratory, and metastatic capacity of breast and prostate cancer cells [24][25][26][27], and can induce tumorigenesis in the mouse prostate [28,29]. However, little is known about the effects of FGF8 in other reproductive tissues, such as the epididymis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Siegel [2], more than 1.6 million new cases of PCa were diagnosed in 2015 in the United States alone. Genetic aberrations, capable of disrupting homeostasis between the epithelial and the stromal prostate compartments, are considered as one of the leading causes of this disease; prostatic stroma is responsible for the quick response in case of tissue injury/damage to the prostatic epithelium [3, 4]. …”
Section: Introductionmentioning
confidence: 99%